DESALINATION OF SEA WATER USING ACTIVATED ZEOLITE BY CLORIDE ACID IN TROPICAL AREA BASED ON COLUMN ION EXCHANGE METHOD - Rasyid, Firnanelty; Aisyah; Irnaningsih; Masri, Melati (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
ABSTRACT The main objective of this study is to reduce the content of salt in the sea water. Zeolite is material which applied by ion exchange method. Activation of zeolite is significant process which making pores of zeolite can accerelate of adsorption. This research used two size of zeolite are 40 and 100 mesh. Zeolite can be activated using chloride acid. The highest concentration can reduce salinity of sea water greater. This happens because the highest concentration of the reactant has stronger binding power so that the particles in the zeolite can absorb quickly. Based on parameters test of salinity of sea water confirmed the ZA with 100 mesh can be used fresh water because its have pH 6.25, tasteless, odorless, colorless, and value of turbidity is lower 0.29. These properties have suitable for water clean for widely consumption of people.